Ultrafiltration membrane cleaning processes optimization in seawater desalination plants - Gilabert-Oriol, Guillem (Walter de Gruyter GmbH, 2021)
This book covers the ultrafiltration membranes, specifically focusing on the elements that are produced using PVDF technology and out-side-in configuration. It specifically targets ultrafiltration technology as a pretreatment of seawater reverse osmosis desalination process. However, what is described in the book can be leveraged in other ultrafiltration membrane types. It explains how to significantly improve the efficiency of the process.